Nghiên cứu chế tạo tổ hợp oxit KFeMnOx trên gốm cao nhôm ứng dụng để hấp phụ SO2 trong không khí - Trung, Nguyễn Quốc; Chi, Trần Quế; Sơn, Hoàng Anh; Sơn, Lê Phúc (Vietnam Journal of Chemistry, 2016)
In this study, KFeMnOx was prepared by sol- gel method through the complexes of K+, Fe2+ and Mn2+ with citric acid and ethylenediamine. Depend on conditional of the process the products had different composition of phase. The mechanism of the process to create materials was based on results by TGA of precursor gel. The characteristic parameters of the products were determinated by XRD, SEM and BET methods. The SO2 absorption results of the created products gave optimal process in this all research. Keywords. KFeMnOx, sol-gel method, absorption SO2.